Recent advances in electrolyte molecular design for alkali metal batteries - Ruan, Digen; Cui, Zhuangzhuang; Fan, Jiajia; Wang, Dazhuang; Wu, Yiying; Ren, Xiaodi (Chemical science (Cambridge), 2024)
In response to societal developments and the growing demand for high-energy-density battery systems, alkali metal batteries (AMBs) have emerged as promising candidates for next-generation energy storage. Despite their high theoretical specific capacity and output voltage, AMBs face critical challenges related to high reactivity with electrolytes and unstable interphases. This review, from the perspective of electrolytes, analyzes AMB failure mechanisms, including interfacial side reactions, active materials loss, and metal dendrite growth. It then reviews recent advances in innovative electrolyte molecular designs, such as ether, ester, sulfone, sulfonamide, phosphate, and salt, aimed at overcoming the above-mentioned challenges. Finally, we propose the current molecular design principles and future promising directions that can help future precise electrolyte molecular design. In response to societal developments and the growing demand for high-energy-density battery systems, alkali metal batteries (AMBs) have emerged as promising candidates for next-generation energy storage.